Contribution of Principal Leadership and School Climate to the Performance of Junior High School Teachers in Padang City - M.Aries Fiqri; Hadiyanto Hadiyanto; M. Aries Taufiq; Irsyad Irsyad; Rahmi Eka Putri (STAI Hubbulwathan Duri, 2024)
Effective educational leadership and a positive school climate are crucial determinants of teacher performance. This research aims to elucidate the contribution of principal leadership and school climate to the performance of state middle school teachers in Padang City. The population for this study comprised all state junior high school teachers in Padang City, totaling 1,058 individuals. A sample of 158 teachers was selected using cluster random sampling techniques. Employing a quantitative correlational approach with an ex-post facto research design, this study analyzed the collected data to determine the relationships between the variables. The results indicate that principal leadership contributes 22.3% to teacher performance, while school climate contributes 68%. Together, principal leadership and school climate account for 62.7% of the variance in teacher performance. The overall teacher performance score was 83.46%, categorized as good. Principal leadership scored 84.16%, also in the good category, and school climate scored 84.66%, deemed conducive. These findings underscore the significant impact of leadership and environmental factors within schools on enhancing teacher performance, suggesting that targeted improvements in these areas could substantially elevate educational outcomes.